Rhadinoplax, a new genus of Progeryonidae Stevcic, 2005, for Carcinoplax microphthalmus Guinot & Richer de Forges, 1981, and a redescription of Paragalene longicrura (Nardo, 1868) (Crustacea: Decapoda: Brachyura: Goneplacoidea) - Castro, Peter; Ng, Peter K. L. (Zootaxa, 2008)
Rhadinoplax, new genus, is described for Carcinoplax microphthalmus Guinot & Richer de Forges, 1981, a species previously included in the family Goneplacidae MacLeay, 1838. The new genus is transferred to the family Progeryonidae Števčić, 2005, superfamily Goneplacoidea. The poorly known progeryonid, Paragalene Kossmann, 1878, is also redescribed and figured.